COMPARING THE EXPLICIT TOOLS VS. IMPLICIT EVALUATION AMONG TURKISH GERIATRIC OUTPATIENTS - Bahat, G. (Innov Aging, 2017)
To reduce potentially inappropriate medication (PIM) use in the older adults, the explicit (criteria-based) tools and the implicit (judgment-based) tools are suggested. The reasons why multidisciplinary geriatric teams decide not to follow STOPP criteria have been studied scarce. We aimed to compare an explicit tool (STOPP) with the implicit comprehensive geriatric evaluation among the Turkish geriatric outpatients thereby analyzing the compliance with the recommendations of the STOPP criteria in older inpatients and the reasons underlying the non-compliance. Older patients (>65-years) admitted to outpatient clinic of a university hospital between June 2000-June 2014 were retrospectively and randomly evaluated for PIM with STOPP version 2 criteria and implicit geriatric evaluation on admission. We analyzed how many STOPP recommendations were accepted by the team, and if they were not accepted, the reasons are identified. We will present the results among a total of n=200 subjects.